Effects of Perlocutionary Hate Speech Media on National Discourse in 2021 on YouTube by Joseph Paul Zhang - Rafiqoh, Eva; Rustono, Rustono; Yuniawan, Tommi (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
According to the Ministry of Technology and Information, the broadcast on Joseph Paul Zhang's YouTube channel contains hate speech. The hate speech has an effect on its listeners. Therefore, this study aims to examine the positive and negative effects of hate speech on the Joseph Paul Zhang channel. This study uses a descriptive-qualitative methodology and note-taking technique. The results of the study found positive effects, namely happy, calm, and relaxed effects, and negative effects, namely deceiving, embarrassing, upsetting, scaring, humiliating, prejudiced, and inviting people to do bad things.